South Quay, Trinidad - (:unkn) unknown (Muir Marshall and Co. Ltd., [Trinidad and Tobago], 2011)
The postcard shows the Port of Spain harbour as well as the area known as South Quay which seems to be under construction.
Colour: Sepia; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Harbors; Cities and towns--Port of Spain; Railroad tracks; Architecture